2009
DOI: 10.2188/jea.je20081037
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of Serum Apolipoprotein Concentrations in Middle-Aged Japanese Twins

Abstract: BackgroundStudies of the genetic and environmental influences on apolipoproteins have been conducted, but few have used data from Japanese twins. The aim of this study was to quantify and compare the genetic and environmental causes of individual differences in the serum concentrations of apolipoproteins in Japanese middle-aged twins.MethodsApo A-I, apo A-II, apo B, apo C-II, apo C-III, and apo E were studied. A total of 142 twin pairs, aged 45 through 65 years, were enrolled: 85 monozygotic pairs (59 male, 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
(34 reference statements)
1
4
0
Order By: Relevance
“…Therefore, the observed within-pair differences in ApoC3 are probably associated with acquired factors that, independently of obesity, genetic background and shared environmental factors, also interfere with glucose homeostasis. Our report is in line with previous studies in Japanese MZ twins showing an ICC for ApoC3 of 0.597 in men and 0.477 in women [29,30]. In addition, APOC3 polymorphisms have been associated with plasma ApoC3, triglyceride metabolism and related cardiovascular risk [31e33].…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the observed within-pair differences in ApoC3 are probably associated with acquired factors that, independently of obesity, genetic background and shared environmental factors, also interfere with glucose homeostasis. Our report is in line with previous studies in Japanese MZ twins showing an ICC for ApoC3 of 0.597 in men and 0.477 in women [29,30]. In addition, APOC3 polymorphisms have been associated with plasma ApoC3, triglyceride metabolism and related cardiovascular risk [31e33].…”
Section: Discussionsupporting
confidence: 92%
“…This classification methodology is known to be 95% accurate in determining twin zygosity. 21 , 22 This study was approved by the Osaka University Ethical Review Committee.…”
Section: Methodsmentioning
confidence: 99%
“…ApoC1 is involved in lecithin cholesterol acyl transferase activation [ 19 ] and cholesterol ester transfer protein inhibition [ 20 , 21 ]. ApoC4 is involved in triglyceride (TG) metabolism [ 22 ] and apoC2 is a cofactor for lipoprotein lipase enzyme [ 23 ]. Although the major contribution of the APOE-C1-C4-C2 gene cluster is in the regulation of LDL-related traits, recent genome-wide association studies (GWAS) also reported their significant associations with TG and HDL-C levels [ 4 , 5 , 8 ]…”
Section: Introductionmentioning
confidence: 99%